QUANTITY OF ANTIOXIDANTS IN TURMERIC AND MUSK LIME PREPARATIONS IN TREATING VANGINAL DISCHARGE - Dewi Puspa Rianda; Muthia Deliana; Rima Novia Putri; Zulya Erda; Astri Yulia Sari Lubis; Ashar Abilowo (Bajang Institute, 2025)
One of the reproductive health problems in women is the occurrence of vaginal discharge which can be experienced by various ages, especially women of childbearing age (WUS). Pathological vaginal discharge is an abnormal vaginal secretion in women. Excessive and abnormal vaginal discharge can be an early symptom of cervical cancer. Abnormal vaginal discharge can be treated with the use of herbs or preparations that function as effective anti-fungi. Turmeric is rich in essential oil content that can reduce vaginal discharge in women because it acts as an anti-bacterial, anti-inflammatory, antioxidant. Vitamin C content in oranges can overcome vaginal discharge. The purpose of the study was to see the characteristics of antioxidants and tannin levels. The research method in this study was an experimental study conducted at the MIPA Laboratory of Pakuan University. The population in this study were turmeric and kasturi orange rhizomes in the plantations of Tanjungpinang City and Bintan Regency. The samples in this study are turmeric and kasturi orange extracts. Turmeric rhizomes will be dried and powdered, while kasturi orange will be filtered to obtain the liquid. These two herbs will be extracted in the laboratory. The results of this study are vitamin C content in fresh oranges of 0.22 mg/100 g with antioxidant activity of 82.93, turmeric powder contains flavonoids with a value of 1116.57 mg/g. Turmeric and orange powder formula (Kujeri) has high antioxidants in the thick extract formula so that it can help kill germs that cause vaginal discharge.